Effects of administering berberine alone or in combination on type 2 diabetes mellitus: a systematic review and meta-analysis - Wang, Jiacheng; Bi, Chenhao; Xi, Hongbin; Wei, Fengqin (Frontiers in Pharmacology, 2024)
Despite the availability of multiple therapies for Type 2 diabetes mellitus (T2DM), challenges remain due to side effects and efficacy limitations. Berberine (BBR) has shown broad anti-diabetic effects, prompting a systematic assessment of its efficacy and safety through a meta-analysis.A comprehensive search was conducted across eight database and search engines from inception until 06/09/2024. Only randomized controlled trials (RCTs) meeting inclusion criteria were analyzed. The Cochrane risk of bias assessment tool and Jadad scale were used to evaluate study quality. Metaanalysis was performed using RevMan v5.3 and Stata/SE v15.1.Fifty studies involving 4,150 participants were included. BBR alone significantly reduced fasting plasma glucose (FPG) (MD = -0.59 mmol/L, p = 0.048), 2-hour postprandial blood glucose (2hPBG) (MD = -1.57 mmol/L, p < 0.01), low-density lipoprotein cholesterol (LDL-C) (MD = -0.30 mmol/L, p < 0.01), total cholesterol (TC) (MD = -0.30 mmol/L, p = 0.034), and triglycerides (TG) (MD = -0.35 mmol/L, p < 0.01). When combined with hypoglycemic drugs, BBR significantly improved FPG (MD = -0.99 mmol/L, p < 0.01), 2hPBG (MD = -1.07 mmol/L, p < 0.01), glycated hemoglobin (HbA1c) (MD = -0.69%, p < 0.01), and other metabolic markers, including fasting insulin (Fins), homeostasis model assessment index for assessing insulin resistance (HOMA-IR), lipid profiles and inflammatory markers. The most common BBR dosage was 0.9-1.5 g/d, with treatment cycles typically lasting 1 to 3 months.